2017
DOI: 10.1038/s41391-017-0015-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevated preoperative neutrophil–lymphocyte ratio predicts upgrading at radical prostatectomy

Abstract: Preoperative NLR ≥ 3 was associated with aggressive PCa, such as upgrading at RP. Even though its effect on clinical-decision making seems to be limited when all clinical and pathological confounders are taken into account, preoperative NLR may still be useful in selected patients to identify aggressive PCa helping patient selection for active surveillance protocols. Conversely, it does not predict BCR when adjusted for the effect of pathological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
4
17
2
Order By: Relevance
“…In our study, we found that increased ANC was helpful in differentiating the malignant disease from those benign ones. Similar to our results, a higher ANC has been reported to discriminate the malignant cases from the benign ones and to be related with the poorer prognosis [15][16][17][18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, we found that increased ANC was helpful in differentiating the malignant disease from those benign ones. Similar to our results, a higher ANC has been reported to discriminate the malignant cases from the benign ones and to be related with the poorer prognosis [15][16][17][18].…”
Section: Discussionsupporting
confidence: 91%
“…In recent studies, NLR has been also suggested to be a marker which should be used for tumor upgrading [16]. Similar to our study, Gökçe et al [17] reported that NLR and ANC were significantly higher in patients with PCa compared to those with BPH.…”
Section: Discussionsupporting
confidence: 90%
“…In humans, no markers equivalent to the mouse Gr1 marker exist, and human neutrophils are defined as CD14-/CD15 + /CD66b + /CD16 + . The neutrophil-lymphocyte ratio in peripheral blood is associated with a high Gleason score and the poor prognosis of men with prostate cancer [60,61]. The ratio is also a prognostic factor of abiraterone and docetaxel treatment in men with castration-resistant prostate cancer [62,63].…”
Section: Neutrophilsmentioning
confidence: 99%
“…Although murine neutrophils differ from human neutrophils in terms of surface markers and genetic diversity [43], evidence suggested that neutrophils play an important role in progression of human prostate cancers. The peripheral blood neutrophil-lymphocyte ratio is associated with a high Gleason score and a poor prognosis in early stage prostate cancer [44,45], and is also a prognostic factor for response to abiraterone and docetaxel treatment in late stage castration-resistant prostate cancer [46,47]. Other studies have shown that neutrophils in both peripheral blood and prostate are predictive factors for prostate biopsy results [48,49].…”
Section: Immune Cells and Intercellular Signaling Promoting Prostamentioning
confidence: 99%